George Rafferty. (1st December 2017) - Richards, Kate
Abstract : A well‐respected, understanding veterinary surgeon who was as comfortable with his clients as with the many species of animals he treated. He was Deputy Lord Lieutenant for Inverness‐shire and was awarded an MBE for his services to agriculture.